IMPLEMENTASI PERATRUARAN DAERAH KABUPATEN SOLOK NO. 4 TAHUN 2013 (STUDI RENCANA INDUK KEPARIWISATAAN TAHUN 2016-2017) - Muhammad Agra Matenas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tourism in Solok Regency is very large and can be said to be famous but the development of tourism itself in Solok Regency is very slow and the vision and mission contained in the Solok District Regulation No. 4 of 2013 therefore by looking at the implementation of the policy direction in the Solok District Regulation No. 4 of 2013 (study of tourism master plans for 2016-2017).            The purpose of this study was to look at the implementation of the policy direction in the Solok District Regulation No. 4 of 2013 (study of tourism master plans for 2016-2017). The research approach is qualitative by describing or writing down the symptoms and conditions in the field by looking at how the implementation of the policy direction in the Solok District Regulation No. 4 of 2013 (study of tourism master plans for 2016-2017).            Primary data is obtained by in-depth interviews with informants, while secondary data from documentation, statistics bureau, and official website of Solok Regency. The data that researchers have collected can be processed and researchers draw conclusions from the data.            The results of this study indicate that the implementation of the policy direction in the Solok District Regulation No. 4 of 2013 (study of the tourism master plan for 2016-2017) the first policy direction of tourism attraction development has been carried out well and in accordance with the strategy of the direction of the policy of empowering tourist attractions contained in the Regional Regulation of Solok No. 4 of 2013 but an insufficient budget has hampered the implementation of the direction of development of tourist attraction policies. Both directions of community empowerment policies have also been implemented well in accordance with the direction of the community empowerment policy, but a lack of public awareness has hampered the direction of community empowerment policies. Keywords: Implementation, Local regulation, Tourism Master Plan